Lavado de suelo contaminado con plomo mediante la utilización de ácido etilendiaminotetraacético (EDTA) - Navarrete Zambrano, Karla Yaneth (2019)
The objective of this research was to evaluate the use of EDTA as a depurating agent for soils contaminated with Pb, in the vehicle mechanic "Cedeño" located in "La Juanita" Km1 Vía Quiroga. An experiment was carried out with two sources of variation (washing time and concentration of EDTA) and one dependent variable. The ANOVA analysis was performed in the statistical program Statistical Package for the Social Sciences (SPSS, 2017) version 21 for the verification of assumptions and analysis of variance among treatments. The study comprised three phases; the first allowed determining the initial concentration of soil lead coming from a vehicle mechanic; the second was based on the efficiency of EDTA in the removal of Pb in contaminated soil. Finally, in the third phase, it was proposed alternatives for minimizing and preventing Pb contamination in vehicle mechanics. It was found that the initial content of Pb was 32.86 mg / kg; subsequently, the four treatments recorded a significant level of Pb removal (between 50%); taking into account the final levels of lead between 13.01-17.02 mg / kg soil. It is concluded that the removal of Pb through the treatments applied reflected a significant efficiency; checking the hypothesis of the study. There was no significance (p> 0.05) between treatments; this indicates that any of the four combinations (0.1% EDTA-24h, 0.1% EDTA-48h, 0.2% EDTA-24h, and 0.2% EDTA-48h) can perform a significant lead removal, reaching levels between 48.24% -53.25%. Treatment 1 (0.1% EDTA-24h) removed a greater amount of lead (53.25%).